Fractional Effective Charges and Misner-Wheeler Charge without Charge Effect in Metamaterials - Igor Smolyaninov (Photonics, 2016)
Transformation optics enables engineering of the effective topology and dimensionality of the optical space in metamaterials. Nonlinear optics of such metamaterials may mimic Kaluza-Klein theories having one or more kinds of effective charges. As a result, novel photon blockade devices may be realized. Here we demonstrate that an electromagnetic wormhole may be designed, which connects two points of such an optical space and changes its effective topological connectivity. Electromagnetic field configurations, which exhibit fractional effective charges, appear as a result of such topology change. Moreover, such effects as Misner-Wheeler “charge without charge” may be replicated.